Democratic Schooling (2016) - Meier, Deborah (Schools (Chicago, Ill.), 2023)
Reflections on the ways in which decisions about the foundation and organization of a small progressive public school exemplify the challenges and trade-offs of living in and with democracy. For the Mission Hill School, democracy was not only an aspiration, it was a way of conducting school life so that every community member felt a sense of belonging and ownership.